Dielectric properties and thermal conductivity of epoxy composites using quantum-sized silver decorated core/shell structured alumina/polydopamine. (March 2019) - Wang, Zhengdong; Yang, Mengmeng; Cheng, Yonghong; Liu, Jingya; Xiao, Bing; Chen, Siyu; Huang, Jialiang; Xie, Qian; Wu, Guanglei; Wu, Hongjing
Abstract: We report the preparation of epoxy-based composites with enhanced dielectric properties and thermal conductivity, by employing intelligently designed core/shell Alumina/Polydopamine (indicated as AO*) and strawberry-like core/shell structured Alumina/Polydopamine/Silver (indicated as AO*@Ag) particles as fillers. The introduction of the core-shell AO* and AO*@Ag particles into the epoxy matrix can distinctly enhance both the dielectric permittivity and dielectric breakdown strength of composites, as compared to that incorporating AO particles as fillers. For example, the dielectric breakdown strength of AO*@Ag/epoxy with 22.9 vol% filler loading is up to 65.5 kV/mm, representing an improvement of 24% compared with AO/epoxy composite at the same filler loading (52.8 kV/mm), while it has enhanced dielectric permittivity at room temperature at low frequency. Additionally, the strawberry-like core/shell particle-filled composites still take on a high thermal conductivity.